1994
DOI: 10.1016/0014-5793(94)01196-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of growth and cysteine proteinase activity of Staphylococcus aureus V8 by phosphorylated cystatin α in skin cornified envelope

Abstract: The activity of a cysteine proteinase purified from Staphylococcus aureus V8 (SAVI) was inhibited by phosphorylated cystatin a (Pqstatin a) and by purified corn&d envelope protein of newborn rat, a conjugated form of P-cyst&in a. Immunohistochemical analysis demonstrated a marked decrease in P-cystatin a content in conrifled envelope treated with sphingosine. The inhibition of papain activity by proteins from sphingosine-treated skin was much weaker than that exerted by proteins from the untreated skin. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…We observed that the activity of cysteine proteases decreased significantly when the microorganisms were cultured in the presence of various concentrations of chicken cystatin and compared to cultures without inhibitor added. Naito et al (1995) showed the growth of Porphyromonas gingivalis, an oral pathogen secreting a large number of proteolytic enzymes, including cysteine proteases, is inhibited by rat cystatin S. In line with this, the phosphorylated rat cystatin A was used successfully to inhibit the growth of Staphylococcus aureus and its cysteine protease activity (Takahashi et al 1994). A number of studies have shown that the N-terminal part of the inhibitor, in particular of members of the cystatin family, is important in interaction with cysteine proteases (Bjork et al 1994).…”
Section: Discussionmentioning
confidence: 91%
“…We observed that the activity of cysteine proteases decreased significantly when the microorganisms were cultured in the presence of various concentrations of chicken cystatin and compared to cultures without inhibitor added. Naito et al (1995) showed the growth of Porphyromonas gingivalis, an oral pathogen secreting a large number of proteolytic enzymes, including cysteine proteases, is inhibited by rat cystatin S. In line with this, the phosphorylated rat cystatin A was used successfully to inhibit the growth of Staphylococcus aureus and its cysteine protease activity (Takahashi et al 1994). A number of studies have shown that the N-terminal part of the inhibitor, in particular of members of the cystatin family, is important in interaction with cysteine proteases (Bjork et al 1994).…”
Section: Discussionmentioning
confidence: 91%
“…Cystatin A has been identified as a minor (2-5%) crosslinked component of CE and suggested to contribute to bacteriostatic properties of skin [7][8][9]. Indeed, Takahashi et al [10] were able to demonstrate that cystatin a (a rat counterpart of cystatin A) depleted rat skin is more sensitive to Staphylococcus aureus colony formation compared to normal skin.…”
Section: Cystatin a (Stefin A)mentioning
confidence: 96%
“…Filaggrin [14] is thought to be a precursor protein which is degraded by epidermal proteinases, such as cathepsin D to free amino acids in the stratum corneum [9,12,[19][20][21]. In addition, cystatin A(α) [24], also known as stefin A [27], which is a cysteine protease inhibitor, suppresses the colonization of the skin by S. aureus [25], and both Ted-H-1 antigen [26] and involucrin are present on the stratum corneum cell membrane and play some role on the defence mechanism of the stratum corneum. Therefore, the expressions of these four proteins in lesional and nonlesional skin of AD patients were determined in this study.…”
Section: Introductionmentioning
confidence: 99%